2015
DOI: 10.3923/ijcr.2016.61.68
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Epithelial Ovarian Carcinoma in India: A Case Control Study in Low-Incidence Population

Abstract: A case-control study to identify the risk factors for ovarian carcinoma in Tiruchirapalli district, Tamilnadu, India a low incidence population was conducted. The invasive epithelial ovarian cancer case patients were 37. The control group consisted of 74 healthy women, matched according to age categories. Subjects were interviewed in person regarding socio demographic and reproductive characteristics. The unconditional logistic regression was performed and tests of statistical significance were based on differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 25 publications
1
16
1
Order By: Relevance
“…Most previous reports were limited to cases in Western countries and the USA. Studies have reported that the annual incidence of ovarian cancer varies with race [ 8 , 40 , 41 ]. The genetic background and heredity of patients may be associated with different frequencies of histological subtypes and FIGO stage and thus influence prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous reports were limited to cases in Western countries and the USA. Studies have reported that the annual incidence of ovarian cancer varies with race [ 8 , 40 , 41 ]. The genetic background and heredity of patients may be associated with different frequencies of histological subtypes and FIGO stage and thus influence prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies support this postulation, such as [26][27][28] The study also indicated that with each year's use of oral contraceptive pills by 7% 26 . The length of use of oral contraceptives is also an essential factor, and The reduced risk can continue for up to 10-15 years after the cessation of pills 27,29 .…”
Section: H5: Ovulation Information Has a Positive Association With The Risk Of Developing Ovarian Cancer In Women In Libyamentioning
confidence: 79%
“…The findings of the study are similar to findings discussed in the literature. such as [26][27][28] .…”
Section: Use Of Hormonal Birth Control As Risk Factor For Ovarian Cancermentioning
confidence: 99%
“…The incidence of ovarian tumours in modern Chennai is around 6.1 per 100 000 females. 2 The 5-year survival rate for ovarian malignancy is 30-40% as they are mostly inoperable at the time of diagnosis. 8 Ovarian tumours may be benign, malignant or borderline malignant.…”
Section: Discussionmentioning
confidence: 99%